Assessment and Comparison of Rapid Weight Loss Methods and its Complications in Various Weight Groups of Adult Elite Wrestlers - Ramin Beyranvand; Ali Moradi; Faraj Fatahi; Rahim Mirnasouri (Shiraz University of Medical Sciences, 2017)
Background: The prevalence of rapid weight loss methods among wrestlers has raised concerns about the health and performance of these people. The purpose of this study was to assessment and comparison of rapid weight loss methods and its general effects in various weight groups of adult elite wrestlers. Methods: In this analytical-descriptive study, the sample consisted of 40 elite wrestlers with mean age of 24.77 years (12 lightweight, 16 middleweight and 12 heavyweight wrestlers), who all had an experience of playing in the national team of the Islamic Republic of Iran for at least three years. The methods and the effects of rapid weight loss were evaluated using the validated Persian version of the Oppliger questionnaire (ICC>0.65). Finally, Kruskal-Wallis and Chi-square tests were used to examine differences between the 3 weight groups using SPSS 21 (p≤0.05). Results: The results of this study showed that the most commonly used methods for weight loss in all three weight groups included increased exercise (79%) and Intense dieting (76.7%). The results also showed that dizziness (74.4%), muscle cramp (69.7%) were the most frequent complications observed in various weight groups following rapid weight loss. Moreover the results showed there was no significant differences between the methods of rapid weight loss and its complications in various weight groups of wrestlers (P>0.05). Conclusion: According to the results of this study it seems that the methods of rapid weight loss and its complications are similar in various weight groups of adult elite wrestlers. Therefore it seems necessary that adequate information about appropriate weight loss methods should be provided for them in order to prevent the complications of rapid weight loss.